1989
DOI: 10.1017/s0033291700024296
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatology of minor psychiatric morbidity: a crosscultural comparison

Abstract: SynopsisThe basic symptoms of minor psychiatric morbidity (MPM) reported elsewhere were also found in a community survey in Taiwan. However, differences in the patterns of and manifestations of the symptoms were evident. Contrary to most Western surveys, the prevalence of anxiety (24·7 %) was found to be higher than that of depression (8·3 %) in Taiwan. Possible explanations based on sociocultural characteristics of the Chinese family were proposed. The notion of somatization as a predominant symptom in Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
61
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 44 publications
4
61
1
Order By: Relevance
“…When Kadir and Bifulco (2010) examined a community sample of Malaysian women, they found that both somatic and psychological symptoms of depression were expressed by these participants. Although this study was qualitative in nature, it is consistent with other community-based studies (e.g., Cheng, 1989;Cheung, 1982) that suggest that the high prevalence of somatization in people of Asian background is not likely observed in community samples.…”
supporting
confidence: 89%
“…When Kadir and Bifulco (2010) examined a community sample of Malaysian women, they found that both somatic and psychological symptoms of depression were expressed by these participants. Although this study was qualitative in nature, it is consistent with other community-based studies (e.g., Cheng, 1989;Cheung, 1982) that suggest that the high prevalence of somatization in people of Asian background is not likely observed in community samples.…”
supporting
confidence: 89%
“…These culturebound syndromes signify spiritual imbalance, nerve weakness, or degenerating nerves (shenjing shuairo); anger, resentment, somatic illness, and neurotic symptoms (hwabyung); and fatigue, anxiety, headache, impotence, and neuralgia (neurasthenia). These culture-bound syndromes have also been empirically linked to classic symptoms of depression based on using both DSM and ICD criteria (Cheng, 1989;Kleinman, 1982;Kim, 2002;Lee & Wong, 1995;Pang, 2000;Yan, 1989;Zhang, 1989). For instance, researchers have found that some 40% to 90% of patients diagnosed as having neurasthenia actually met the criteria for depression and showed marked improvement when treated with antidepressants (Kleinman, 1982).…”
Section: Asiansmentioning
confidence: 99%
“…Studies from Japan and Taiwan [67,68] report lower frequency of depressive symptomatology in the elderly population compared with studies from Western Europe and the US. The authors attributed these discrepancies to differences in the structure of the family (larger families with stronger bonds in Japan) and to the increased activity of the Japanese elderly.…”
Section: Clinical Symptomatologymentioning
confidence: 99%